Análisis y propuesta de infraestructura tecnológica para la unidad de inteligencia financiera del Perú - Saavedra García, Luis Alberto (2005)
The present work was made with the purpose of being exposed like thesis subject to obtain the title of Systems engineer. The election of the subject was really made taking into account the necessity of a task that allowed to demonstrate the capacity us of management of technological resources based on a national and contemporary reality to obtain a viable product, feasible and useful. For it the technological capacity was considered nonsingle which it has, but that in addition take into account the necessity to the client by a product that can be maintained in the time, updating itself easily with no need to conserve its competitive capacity of investments which they significantly hit the economic stability of the client or which they imply important changes of reingenierÌa, establishing a scheme of minimum investment with Maxima economic gain and of added value. A managemental vision with the idea always stayed to present/display a work that allows the interrelation of both worlds: the one of the technology like manager of the talent, the knowledge and the innovation of machines and tools, as well as the world of the management like manager of resources and economic strategies. The created problem of investigation, is of practical character and looks for to lately satisfy a necessity arisen in Peruvian the economic and financial sector due to the invasion by means of manifold and falsified mechanisms, of the financial markets with capitals badly had. This reality has an international importance since the criminal organizations who practice these techniques, are units organized that they have to be able technological, economic and influences in all the social and political layers very well; simultaneously one is framed like a world-wide problem that affects and is affected reason why it follows one another in the different nations. The globalization and its implications and tools more and more make the fight against the flagellum difficult of the legitimation of capitals, reason why having a technological platform is made important more and more that it allows to a preventive and curative control for the cleaning and maintenance of the financial schemes and economic values of the currency without losing the balance between the value of the money his real spending power. In the present project a proposal considers that it tries to be economic and viable, updateable and safe, reliable and efficient for the installation of a platform of information by means of the technology of the digital communications and the security of the information for the Unit of Financial Intelligence in Peru. An interphase considers man machine that is friendly, that does not require of great training or specialization; that it does not involve to an important list of personnel specialized in the maintenance of the same one and where integration with the foreign users does not imply important of its systems or installed modifications, operating, planned or existing. This raised to use technology of end in hardware and software, doing use of means of universal transference of economic information and like the Internet and with the protocols of security and own communications of this means; guaranteeing the stability of the platform by means of the correct integration of technologies, the best propietary mechanisms of security of the information, the universalidad of the communications that obtains with the navigators and the best support than can offer the open atmospheres who make possible the integration of different operating systems existing in the market and or installed thus to diminish in expenses (caused by the purchase of new platforms) which they could hit in the private or public units of work, diminishing the bureaucratic proceedings and letting the minimum of lagoons in the process of implantation of the regulating norms of the information to manipulate and election of the centralizador being like the one of greater importance and hierarchy in the raised network.